The impact of renewable energy sources on economic growth and CO2 emissions:Evidence from Iberian Peninsula - Silva, Filipa Inês Gil (2012)
During the last years, due to a constant increase of the concern about environmental questions and an accompanying development of related policies, there has been an increase in energy production from renewable sources. In this line of thought, the aim of this dissertation is to examine the relationship between renewable energy production, economic growth and CO2 emissions in the Iberian Peninsula, using a Structural Vector Autoregressive model. The innovative contribution of this dissertation is the incorporation of oil prices, as an exogenous variable, since the increase in the price of this raw material in the international market have had very negative impacts on the economies of both countries. This study covers the sample period from 1960 to 2009 and it approaches two distinct analyses: one for aggregate energy production (TRES), considering the total of renewable energy sources; another for disaggregated energy sources, considering hydroelectricity separately from the other renewable sources, due to the high weight of the first in energy production. For the two cases, both the structural factorization results and the impulse-response functions show that, contrary to what was expected, a shock on energy does not have a significant impact on GDP. Total RES and hydro only affect negatively CO2 emissions during the first year. This situation led to conclude that hydroelectric is the main source that contributes to the total RES. Another important result is the positive impact of CO2 emissions to a shock on GDP that occurs at least most during six years. The variance decomposition shows, for both countries, a large amount of uncertainty in the forecast of the growth rate of CO2 emissions, mainly due to a shock on TRES (30% in Portugal and 20% in Spain) for aggregate analysis and due to a shock on hydro (28% in Portugal and 20% in Spain) for disaggregate analysis and almost no uncertainty in predicting the growth rate of TRES and GDP.